US intrafirm trade: sectoral, country and location determinants in the 90s - Filipe, João Paulo (2010)
This paper studies the evolution and determinants of US intrafirm trade between 1989-98. We will extend previous similar econometric testing not only by using more recent data but also by considering inter-country differences in addition to inter-sectoral variation of intrafirm trade. At the sectoral level, relevant factors appear to be technology intensity, the level of vertical integration, economies of scale and the level of international production, as well as the impact of the geographic concentration of US parent firms. At the country level, the size of the market and some country specificities appear to favor intrafirm trade while increasing levels of the tax rate on profits of the foreign country and economic distance disincentives this trade.